Efficient synthesis of pyrazolopyridines containing a chromane backbone through domino reaction - Navari, Razieh; Balalaie, Saeed; Mehrparvar, Saber; Darvish, Fatemeh; Rominger, Frank; Hamdan, Fatima; Mirzaie, Sattar (Beilstein Journal of Organic Chemistry, 2019)
An efficient approach for the synthesis of pyrazolopyridines containing the aminochromane motif through a base-catalyzed cyclization reaction is reported. The synthesis was carried out through a three-component reaction of (arylhydrazono)methyl-4H-chromen-4-one, malononitrile, primary amines in the presence of Et3N at room temperature. However, carrying out the reaction under the same conditions without base led to a fused chromanyl-cyanopyridine. High selectivity, high atom economy, and good to high yields in addition to mild reaction conditions are the advantages of this approach.
Keywords: chromane; domino reaction; fused heterocyclic skeletons; pyrazolopyridines